Our quest for success: Using a multidisciplinary students-as-partners model to develop an innovative online learning game - Burling, Meredith G.H.; Rahouma, Lina; Good, Arla; Kasper, Joleine C; Kranyak, Samantha; Ramnarine, Kieran; Bramesfeld, Kosha (International Journal for Students as Partners, 2019)
In their review of the students-as-partners literature, Mercer-Mapstone et al. (2017) found that only 5-6% of published research articles on student-partnership models focused on multidisciplinary partnerships. This case study, authored by five undergraduate students and two academics, sought to examine the utility of using a multidisciplinary students-as-partners approach to advance the development of an online learning game focused on food insecurity. The multidisciplinary nature of the partnership facilitated perceptions of an equitable partnership, contributed to innovative design ideas, and conferred several benefits to the collaborators beyond those traditionally seen in the students-as-partners literature (Mercer-Mapstone et al., 2017). However, the multidisciplinary nature of the partnership also posed unique mentoring and coordination challenges that should be considered when adopting a multidisciplinary approach to teaching innovation.